ONE STOP LEARNING ENGLISH IN SIDOARJO ENGLISH COMMUNITY (SIDEC) - Winda Sulistyoningsih; Kuni Fauziyati; Dina Astriana (STKIP PGRI Sidoarjo, 2019)
The implementation of the community service program entitled 'One Stop Learning English in Sidoarjo English Community (SIDEC) aims to share about learning English, more precisely a day training that prioritizes English language skills, especially speaking skills of SIDEC members consisting of various professions.. There are many problems that club members often encounter in speaking English pronunciation and using vocabulary functions. In its implementation, this One Stop Learning English training contains listening, reading, speaking, structure and writing. But it is focused on speaking, with an allocation of 2,5 hours, starting at 16:30 to 21:00.